Chapter 7: Problem 6
Find the power series in \(x\) for the general solution. $$ \left(1+x^{2}\right) y^{\prime \prime}+2 x y^{\prime}+\frac{1}{4} y=0 $$
Chapter 7: Problem 6
Find the power series in \(x\) for the general solution. $$ \left(1+x^{2}\right) y^{\prime \prime}+2 x y^{\prime}+\frac{1}{4} y=0 $$
All the tools & learning materials you need for study success - in one app.
Get started for freeIn Exercises 47-51 find a fundamental set of Frobenius solutions. Compute the coefficients \(a_{0}, \ldots, a_{2 M}\) for \(M\) at least 7 in each solution.$$ \text { C } 8 x^{2}\left(1+2 x^{2}\right) y^{\prime \prime}+2 x\left(5+34 x^{2}\right) y^{\prime}-\left(1-30 x^{2}\right) y=0 $$
(a) Use Exercise 28 to show that the power series in \(x\) for the general solution of $$ \left(1-x^{2}\right) y^{\prime \prime}-2 b x y^{\prime}+\alpha(\alpha+2 b-1) y=0 $$ is \(y=a_{0} y_{1}+a_{1} y_{2},\) where $$ y_{1}=\sum_{m=0}^{\infty}\left[\prod_{j=0}^{m-1}(2 j-\alpha)(2 j+\alpha+2 b-1)\right] \frac{x^{2 m}}{(2 m) !} $$ and $$ y_{2}=\sum_{m=0}^{\infty}\left[\prod_{j=0}^{m-1}(2 j+1-\alpha)(2 j+\alpha+2 b)\right] \frac{x^{2 m+1}}{(2 m+1) !} $$ (b) Suppose \(2 b\) isn't a negative odd integer and \(k\) is a nonnegative integer. Show that \(y_{1}\) is a polynomial of degree \(2 k\) such that \(y_{1}(-x)=y_{1}(x)\) if \(\alpha=2 k\), while \(y_{2}\) is a polynomial of degree \(2 k+1\) such that \(y_{2}(-x)=-y_{2}(-x)\) if \(\alpha=2 k+1\). Conclude that if \(n\) is a nonnegative integer, then there's a polynomial \(P_{n}\) of degree \(n\) such that \(P_{n}(-x)=(-1)^{n} P_{n}(x)\) and $$ \left(1-x^{2}\right) P_{n}^{\prime \prime}-2 b x P_{n}^{\prime}+n(n+2 b-1) P_{n}=0 $$ (c) Show that (A) implies that $$ \left[\left(1-x^{2}\right)^{b} P_{n}^{\prime}\right]^{\prime}=-n(n+2 b-1)\left(1-x^{2}\right)^{b-1} P_{n} $$ and use this to show that if \(m\) and \(n\) are nonnegative integers, then $$ \begin{array}{l} {\left[\left(1-x^{2}\right)^{b} P_{n}^{\prime}\right]^{\prime} P_{m}-\left[\left(1-x^{2}\right)^{b} P_{m}^{\prime}\right]^{\prime} P_{n}=} \\\ {[m(m+2 b-1)-n(n+2 b-1)]\left(1-x^{2}\right)^{b-1} P_{m} P_{n}} \end{array} $$ (d) Now suppose \(b>0\). Use (B) and integration by parts to show that if \(m \neq n\), then $$ \int_{-1}^{1}\left(1-x^{2}\right)^{b-1} P_{m}(x) P_{n}(x) d x=0 $$ (We say that \(P_{m}\) and \(P_{n}\) are orthogonal on (-1,1) with respect to the weighting function \(\left.\left(1-x^{2}\right)^{b-1} .\right)\)
In Exercises \(61-68\) use the method suggested by Exercise 60 to find the general solution on some interval \((0, \rho)\) $$ 9 x^{2}(5+x) y^{\prime \prime}+9 x(5+3 x) y^{\prime}-(5-8 x) y=0 $$
In Exercises 47-51 find a fundamental set of Frobenius solutions. Compute the coefficients \(a_{0}, \ldots, a_{2 M}\) for \(M\) at least 7 in each solution. $$ \text { C } 9 x^{2}\left(1+x^{2}\right) y^{\prime \prime}+3 x\left(3+13 x^{2}\right) y^{\prime}-\left(1-25 x^{2}\right) y=0 $$
Find a fundamental set of Frobenius solutions. Give explicit formulas for the coefficients. \(x^{2}(1-x) y^{\prime \prime}-x(3-5 x) y^{\prime}+(4-5 x) y=0\)
What do you think about this solution?
We value your feedback to improve our textbook solutions.